STRATEGI STRATEGI PENINGKATAN MAKP CAKUPAN ASUHAN KEPERAWATAN PROFESIONAL BERBASIS SDKI SLIKI DAN SIKI DI RSUD KAB. BULELENG SINGARAJA - S, Dwi Oktavyanti; Puspita, Yenni; Masrukin, Moch; Setu, Yohana Teodosia; Syairozi, Ahmad (Jurnal Abdi Mahosada, 2023)
Documentation of nursing care based on SDKI SLIKI and SIKI has not been implemented optimally in Buleleng District Hospital. Seminars and training on nursing care documentation based on SDKI SLIKI and SIKI will help optimize nursing care documentation in a professional manner for nurses and nurses can focus on providing professional nursing services to patients. Nurses who are the spearhead in health services need to make changes by providing nursing services in the form of a model of professional nursing care methods through the implementation of SDKI SLIKI and SIKI in order to provide maximum and optimal nursing care. The purpose of this activity is to increase MAKP in the scope of implementing professional nursing care documentation based on SDKI SLIKI and SIKI in Buleleng District Hospital. The method used in this activity was a group discussion which previously carried out pretests and posttests on SDKI SLIKI and SIKI. Through MAKP seminars and training based on SDKI SLIKI and SIKI MAKP and documentation of professional nursing care based on SDKI SLIKI and SIKI and starting to be implemented in their respective rooms and nurses can focus on providing nursing care services.